Magnetic Resonance Imaging Findings of Foetal Congenital Toxoplasma Encephalitis: A Case Report - Lin, Min-Jie; Lin, Jian; Zheng, Ke (Current Medical Imaging, 2024)
BackgroundToxoplasma gondii (T. gondii) infection is not uncommon in daily life, primary infection with T. gondii acquired during gestation may lead to a series of fetal complications. Prenatal ultrasound and postpartum neonatal T. gondii encephalitis have been reported previously, but fetal MRI findings of T. gondii encephalitis are quite rare. It is important to identify the severity of cerebral damage and assess fetal prognosis.ObjectiveThe purpose of this report is to emphasize that MRI can provide more excellent anatomic information on abnormalities in cerebral parenchyma than ultrasound, which is helpful for the diagnosis of prenatal infectious encephalitis.Case PresentationA 38-year-old woman presented to our hospital at a gestation age of 29 weeks due to an ultrasound that showed fetal ventriculomegaly. The fetus demonstrated ventriculomegaly, intrauterine growth restriction, and multiple cystic lesions close to the corticomedullary junction of the frontal, temporal and parietal lobes on both sides. The woman chose to terminate the pregnancy, and pathological examination confirmed the diagnosis of congenital toxoplasma encephalitis.ConclusionThis is a rare report of MRI manifestations of fetal congenital toxoplasma encephalitis. Detailed knowledge of MRI findings in fetal congenital toxoplasma encephalitis is helpful for prenatal consultation and pregnancy management.
Keywords: Case report